Model reference tracking control of linear motor with dead-zone via switched systems subjected to time-varying delay - Teng, Long (2020)
In this paper, model reference tracking control of linear brushless DC motor with dead-zone is investigated. Compared with traditional control methods which requires the nonlinear model of dead-zone and then compensation is executed, the dead-zone is modeled as time-varying input delay systems. Thus the complex nonlinearities of dead-zone can be ignored. As a result, the whole motor motion can be regarded as switched systems comprised of two subsystems, one is a linear time-varying input delay system when motor enters the dead-zone, and the other one is a linear non-delayed system when motor leaves the dead-zone. The tracking control problems for both subsystems are considered. In particular,a stabilization method based on Lyapunov-Razumihkin function is adopted for system with time-varying delay, which leads to easier implementations of controller synthesis and computation when compared to Lyapunov-Krasovskii function. Simulation and experimental results on a linear motor is provided to illustrate the effectiveness of the proposed method.